2007
DOI: 10.1017/s1751731107000572
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of growth rate variation between commercial pig herds

Abstract: The study was designed to provide quantifiable information on both within-and between-herd variation in pig growth rate from birth to slaughter and to examine how this was influenced by moving pigs at a common age to a common environment. Five litters were selected from each of eight pig herds in Northern Ireland with varying growth performance. All eight herds were offered the same nutritional regime. Five pigs (three boars and two gilts) were selected from each litter. In each herd, 22 pigs (12 boars and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…Both parameters in the last five years in Spain have globally improved during the fattening phase but not changed during the nursery phase. Moreover, we have observed variation in ADG and FCR between pig producing companies that could be attributed to management, health, genetic and facilities issues as described previously by other authors [12]. The same evolution for ADG and FCR has been observed for most of the main pig producing countries in Europe during the period 2010–2014 [8].…”
Section: Discussionsupporting
confidence: 81%
“…Both parameters in the last five years in Spain have globally improved during the fattening phase but not changed during the nursery phase. Moreover, we have observed variation in ADG and FCR between pig producing companies that could be attributed to management, health, genetic and facilities issues as described previously by other authors [12]. The same evolution for ADG and FCR has been observed for most of the main pig producing countries in Europe during the period 2010–2014 [8].…”
Section: Discussionsupporting
confidence: 81%
“…Uniformity has been described using the coefficient of variation, likewise in the studies of Alfonso et al (2010), Magowan et al (2007), and Patience et al (2004), and differences in uniformity across the dietary groups were tested by comparing CI of CV (Alfonso et al, 2010). The average CV for CW found in the present study is consistent with that reported for CW of Italian heavy pigs by Virgili et al (2003).…”
Section: Uniformity Of Carcasses and Primal Cutssupporting
confidence: 84%
“…Knowledge about the variance-covariance matrix of parameters is of interest to generate other populations of pigs, but it remains to be confirmed whether the variance-covariance matrix is specific for this population of pigs or that (part of) it has general applicability. Magowan et al (2007) highlighted the difficulty to assess the extent to which differences in feed intake and growth rate between and within herds can be attributed to genetics, relative to the effects of management and disease. The relations between parameters observed here are therefore foremost phenotypic relations.…”
Section: Discussionmentioning
confidence: 99%